Community Structure of Seagrass in Harapan Island, Seribu Islands, Indonesia - Ratih Ida Adharini; Tesya Ranma Yuniarga; Nindya Larasaty Prasetya; Faizal Rachman (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2022)
Seagrass is an aquatic biota that is ecologically and economically beneficial. This study aims to determine the community structure of seagrass in Harapan Island, Seribu Islands, Indonesia. The research was conducted using purposive sampling method, that divided into two sites which is considered to represent the ecology’s condition of Harapan Island. The site 1 was located adjacent to the mangroves area, while the site 2 was placed near a reclamation development and ship anchoring. Every site had three subsites as replications, each was 50 meters apart. Water parameters temperature, salinity, turbidity, pH, dissolved oxygen (DO), depth, and organic compound of each site were measured. The results showed that coverage of seagrass in site 2 is higher than site 1 that categorized as frequent-common coverage. The site 2 had the density of 220 individuals seagrass per square meter that dominated by Cymodocea rotundata. The highest diversity index was found in the site 1 at 1.15, with the lowest dominance index being 0.39. The distribution pattern in site 1 is clustered and uniform, while site 2 is uniform. The Importance Value Index in site 1 was 114,8 by Halodule uninervis, while site 2 was 125,5 by C. rotundata. It is thought that the low diversity of seagrass at the site 2 due to it was near a reclamation development and ship anchoring that disturb the abundance and community structure of seagrass in Harapan Island. Habitat destruction and anthropogenic impact of seagrass need to be minimized to support environmental coastal and fisheries sustainability.